2017
DOI: 10.1016/j.bpj.2016.11.707
|View full text |Cite
|
Sign up to set email alerts
|

Markov State-Based Quantitative Kinetic Model of Sodium Release from the Dopamine Transporter

Abstract: The dopamine transporter (DAT) belongs to the neurotransmitter:sodium symporter (NSS) family of membrane proteins that are responsible for reuptake of neurotransmitters from the synaptic cleft to terminate a neuronal signal and enable subsequent neurotransmitter release from the presynaptic neuron. The release of one sodium ion from the crystallographically determined sodium binding site Na2 had been identified as an initial step in the transport cycle which prepares the transporter for substrate translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The stability of the OC state promotes the solvation of the intracellular vestibule, thereby weakening the hydrogen bonding network involving various intracellular gating residues (Arg79-Glu452, Glu80-Lys275, Asp87-Trp282, Tyr350-Glu444). Opening of the intracellular permeation pathway is associated with displacement of Na + from the Na2 site into the cytoplasm (consistent with extensive experimental evidence (36,40,67)), followed by cytosolic exit of APP+. Simulations show contacts made by the neurotransmitter to specific subsites (32) within the orthosteric binding pocket change as import progresses.…”
Section: Deep Mutagenesis Supports the Simulated Binding Mechanism Of Na + And Neurotransmittersupporting
confidence: 78%
See 1 more Smart Citation
“…The stability of the OC state promotes the solvation of the intracellular vestibule, thereby weakening the hydrogen bonding network involving various intracellular gating residues (Arg79-Glu452, Glu80-Lys275, Asp87-Trp282, Tyr350-Glu444). Opening of the intracellular permeation pathway is associated with displacement of Na + from the Na2 site into the cytoplasm (consistent with extensive experimental evidence (36,40,67)), followed by cytosolic exit of APP+. Simulations show contacts made by the neurotransmitter to specific subsites (32) within the orthosteric binding pocket change as import progresses.…”
Section: Deep Mutagenesis Supports the Simulated Binding Mechanism Of Na + And Neurotransmittersupporting
confidence: 78%
“…In addition, structural, biochemical and pharmacological studies have shown that substrates entering the outward-facing extracellular vestibule engage an allosteric (or S2) site immediately adjacent to critical gating residues, before moving past the open gate to the orthosteric site (26,(33)(34)(35). Cryo-EM analysis of detergent-solubilized SERT in the presence of ibogaine, a psychoactive plant product that stabilizes IF conformations, allowed for the characterization of OF, OC and IF-like states at moderate resolution (19), showing that regions already implicated in bacterial and mammalian NSS homologues through multiple methods (18,(36)(37)(38)(39)(40)(41) move to open a solvent-accessible intracellular vestibule. In particular, transmembrane helix (TM) 1a moves away from the helical bundle.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] Structural investigations into human NSS transporters have further benefited from the more recent resolution of outward-facing conformations of eukaryotic monoamine transporters Drosophila DAT (d DAT) and human SERT (hSERT). [48][49][50] The screening and dock-ing studies using these crystal structures provide the structural basis of antidepressant recognition and inhibition. [51][52][53][54][55][56] Most recently, cryogenic electron microscopy (cryo-EM) structures of hSERT complexed with the psychedelic non-competitive inhibitor ibogaine reveal the occluded and inward-facing states with similar structural arrangements as seen in LeuT.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described long timescale atomistic MD simulations of hDAT in which we observed spontaneous inward-opening and release of Na þ from Na2 into the intracellular environment (10). Subsequently, we constructed a kinetic model for the release process of Na þ /Na2 and inward-opening of hDAT by using the Markov State Model (MSM) approach on an ensemble of MD simulations totaling >50 ms, and exhibiting multiple spontaneous Na þ /Na2 release events (13). The MSM analysis revealed a complex molecular mechanism in which Na þ /Na2 release can occur via several alternative pathways, each displaying different degrees of net flux that appear to be enabled by different modes of Submitted July 26, 2017, and accepted for publication October 18, 2017.…”
mentioning
confidence: 99%
“…The TCF analysis of 50 ms of MD trajectories of hDAT described in ( 13) serves first to quantify the thermodynamic coupling between Na þ /Na2 release and inward-opening, and second to identify the coordinating residues in the Na2 site that mediate the coupling. CVs were constructed from time structurebased independent component analysis (tICA) (16) performed previously (13). The first CV, denoted as ''Na þ /Na2 release,'' combines distances between Na þ /Na2 and coordinating residues in Na2, as well as Na þ /Na2 and Na þ /Na1; the second CV, denoted as inward-opening, combines distances between the intracellular gate residues (see Fig.…”
mentioning
confidence: 99%